Mean length of utterance in bengali speaking mentally retarded children. - Pitu N (Journal of All India Institute of Speech and Hearing, 1970)
The present study was aimed at determining the mean length of utterance and syntactic complexity in the speech of groups of normals and the mentally retarded population, in the age range of 5-12 years. 20 normal children and 10 mentally retarded children (5 mild and 5 moderately retarded) with IQ range of 40-66 with mean IQ of 53.3 were studied. A language sample consisting of spontaneous and narrated/elicited utterances was recorded from each of the 30 children. 100 utterance of each subject were analyzed for mean length of utterance and syntactic complexity. Mean length was calculated interms of both words and morphemes. Syntactic complexity was assessed with reference to the frequency of different lexical categories, order and arrangements of these lexical categories in the utterances and the number of compound word usage for both the groups.